An algorithm to measure unsymmetrical circle shape of intravascular ultrasound image using image processing techniques - Kutty, Suhaili Beeran; O. K. Rahmat, Rahmita Wirza; Kassim, Sazzli Shahlan; Madzin, Hizmawati; Hamdan, Hazlina (Institute of Advanced Engineering and Science, 2021)
In diagnosing coronary artery disease, measurement of the cross-sectional area of the lumen, maximum and minimum diameter is very important. Mainly, it will be used to confirm the diagnosing, to predict the stenosis if any and to ensure the size of the stent to be used. However, the measurement only offers by the existing software and some of the software needs human interaction to complete the process. The purpose of this paper is to present the algorithm to measure the region of interest (ROI) on intravascular ultrasound (IVUS) using an image processing technique. The methodology starts with image acquisition process followed by image segmentation. After that, border detection for each ROI was detected and the algorithm was applied to calculate the corresponding region. The result shows that the measurement is accurate and could be used not only for IVUS but applicable to solid circle and unsymmetrical circle shape.